IDENTITY REPRESENTATION IN THE SPEECH OF THE LAW: SOCIAL (IN)(EX)CLUSION ON SCENE - Diego de Almeida, Willian (Revista Gênero e Interdisciplinaridade, 2023)
This work proposes a discursive-deconstructivist analysis of the Maria da Penha Law in relation to the representation of indigenous women, in order to trace the effects of discrimination that materialize in the law’s archive. We start from the hypothesis that the law marginalizes indigenous women, through a discursive device that promotes a process of nationalization of the identity/subjectivity of a subject considered peripheral. The work is anchored in the transdisciplinarity between: discursive perspective; Derridean deconstruction (2001, 2007); Foucauldian archegenealogy (2002, 2008, 2015); Anzaldúa’s (2005) and Mignolo’s (2003) theoretical-culturalist point of view. Results show that the text of the law mobilizes the effects of discrimination against indigenous women, as a discursive practice that insists on remaining in the fabric of social formation.